2014
DOI: 10.18632/oncotarget.1957
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage modulates interactions between microRNAs and the 26S proteasome

Abstract: 26S proteasomes are known as major non-lysosomal cellular machines for coordinated and specific destruction of ubiquitinylated proteins. The proteolytic activities of proteasomes are controlled by various post-translational modifications in response to environmental cues, including DNA damage. Besides proteolysis, proteasomes also associate with RNA hydrolysis and splicing. Here, we extend the functional diversity of proteasomes by showing that they also dynamically associate with microRNAs (miRNAs) both in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…Recently, proteasome, other than to regulate proteins performing miRNA biogenesis and functioning, was found to bind miRNAs; and according to our data, it degrades pri‐ and mature, but not pre‐miR‐1 in vitro . Proteasome primarily known as a proteolytic complex has RNase activity both in plants and in mammals .…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Recently, proteasome, other than to regulate proteins performing miRNA biogenesis and functioning, was found to bind miRNAs; and according to our data, it degrades pri‐ and mature, but not pre‐miR‐1 in vitro . Proteasome primarily known as a proteolytic complex has RNase activity both in plants and in mammals .…”
Section: Introductionsupporting
confidence: 60%
“…29,144 Moreover, it can also answer the question raised in our work where we have found the ratio between mature and immature miRNAs to depend on the duration of anoxia-reoxygenation. 145 Recently, proteasome, other than to regulate proteins performing miRNA biogenesis and functioning, was found to bind miRNAs 146 ; and according to our data, it degrades pri-and mature, but not pre-miR-1 in vitro. 147 Proteasome primarily known as a proteolytic complex has RNase activity both in plants and in mammals.…”
Section: Stress Response Factors Directly Affecting Mirnasmentioning
confidence: 51%
“…Recently, Anna S et al reported that microRNAs plays an important role in the regulation of proteasome activity [9]. Furthermore, miR-29b replacement inhibits proteasomes in myeloma cells by targeting PSME4 that encodesPA200 [10].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs also have roles in the cellular response to chemotherapy as well as cell adhesion and metastasis, which makes them a particularly promising set of biomarkers for cancer [70][71][72][73][74][75][76][77]. The discovery that altered levels of miRNAs are associated with certain cancers, including pulmonary, liver and ovarian cancer, has turned focus to the use of miRNA as a new, powerful diagnostic and prognostic tool [78][79][80][81].…”
mentioning
confidence: 99%